A cross-sectional survey of parental attitudes towards Human papillomavirus vaccination exclusion categories in Brazil - Mariana V. Gattegno; Maria A. F. Vertamatti; Robert A. Bednarczyk; Dabney P. Evans (BMC International Health and Human Rights, 2019)
Abstract Background In 1988, Brazil established a constitutional right to health and universal access to health care for all Brazilians through the creation of the Unified Health System (SUS). As part of its efforts to fulfill this right, the quadrivalent Human papillomavirus (HPV) vaccine was introduced into the national immunization program in 2014. The non-discriminatory provision of healthcare goods, facilities, and services is a fundamental part of the right to health. Yet HPV vaccination was limited to females aged 9–13, despite the universal nature of SUS and scientific support for the vaccination of males and older females. The purpose of this cross-sectional study was to describe parental attitudes regarding age- and gender-based HPV vaccination exclusions, as well as parental knowledge of HPV and the HPV vaccine. Methods Data were gathered from parents with children aged 9–17 in a health post located in the municipality of Mauá (São Paulo, Brazil) through interviewer-administered questionnaires. We analyzed attitudes regarding HPV vaccination and its eligibility guidelines by comparing parents of HPV vaccine eligible and ineligible children. Results In this low-income population, the majority of the 219 parents surveyed supported the inclusion of males and females over 13 into the HPV vaccination program; support for the non-discriminatory provision of the HPV vaccine was high among parents – especially if financially accessible. Additionally, there were high levels of knowledge and positive parental attitudes regarding HPV vaccination safety and efficacy among both parent groups suggesting information accessibility – a key component of the right to health and informed decision-making. Conclusions Support for the expansion of HPV vaccination for excluded populations exists, and is not based on current eligibility, or differential knowledge and attitudes about the vaccine. Moving forward, careful consideration of gender- based eligibility for vaccination, informed decision-making, and the importance of community participation in health policy development and implementation may be gleaned from the case of Brazil and beyond.